Improving Contract Administration: Information System Approach on Legal Information - Chong, Heap Yih (International Information Institute, 2012)
An effective contract administration requires proper use of the legal information. However, the information is unstructured and poorly drafted, which caused poor understanding and it may lead to a dispute. Therefore, the paper aims to identify means of enhancing the understanding and appreciation of legal information from the contract documents; and, to develop a template of database system that incorporated the proposed means for improving the practice of contract administration. The template received positive feedback. It is concluded the information system approach on legal information is novel in terms of the proper extraction and use of the information for contract administration.